Integrative Study of Genotypic and Phenotypic Diversity in the Eurasian Orchid Genus Neotinea - Trávníček, Pavel; Chumová, Zuzana; Záveská, Eliška; Hanzlíčková, Johana; Kupková (Jankolová), Lucie; Kučera, Jaromír; Gbúrová Štubňová, Eliška; Rejlová, Ludmila; Mandáková, Terezie; Ponert, Jan (Frontiers in Plant Science, 2021)
Knowledge of population variation across species' ranges is a prerequisite for correctly assessing the overall variability of any group of organisms and provides an invaluable basis for unraveling evolutionary history, optimising taxonomy and devising effective conservation strategies. Here, we examine the genus Neotinea, which represents a relatively recently delimited monophyletic genus of orchids, for which a detailed study of its overall variability was lacking. We applied a suite of biosystematic methods, consisting of flow cytometry, multivariate and geometric morphometrics, and analysis of genomic SNP data, to identify phylogenetic lineages within the genus, to delineate phenotypic variation relevant to these lineages, and to identify potential cryptic taxa within lineages. We found clear differentiation into four major lineages corresponding to the groups usually recognized within the genus: N. maculata as a distinct and separate taxon, the N. lactea group comprising two Mediterranean taxa N. lactea and N. conica, the N. ustulata group comprising two phenologically distinct varieties, and the rather complex N. tridentata group comprising two major lineages and various minor lineages of unclear taxonomic value. Neotinea conica constitutes both a monophyletic group within N. lactea and a distinct phenotype within the genus and merits its proposed subspecies-level recognition. By contrast, the spring and summer flowering forms of N. ustulata (var. ustulata and var. aestivalis) were confirmed to be distinct only morphologically, not phylogenetically. The most complex pattern emerged in the N. tridentata group, which splits into two main clades, one containing lineages from the Balkans and eastern Mediterranean and the other consisting of plants from Central Europe and the central Mediterranean. These individual lineages differ in genome size and show moderate degrees of morphological divergence. The tetraploid N. commutata is closely related to the N. tridentata group, but our evidence points to an auto- rather than an allopolyploid origin. Our broad methodological approach proved effective in recognizing cryptic lineages among the orchids, and we propose the joint analysis of flow cytometric data on genome size and endopolyploidy as a useful and beneficial marker for delineating orchid species with partial endoreplication.